Criminologia, feminismo e raça: guerra às drogas e o superencarceramento de mulheres Latino-Americanas - Araújo, Bruna Stéfanni Soares de (2017)
This dissertation is dedicated to understanding the growing phenomenon of criminalization of latin american women for related crimes to drugs and a need for a review of the epistemological foundations of feminist criminology, knowledge of the field that has been placed as the protagonist of the studies on this subject. From the modern criminology construction analysis through the its reference epistemic created hiccup a eurocentric perspective, we highlight how reviews arising from a marginalized perspective and seeks to break the ideological hegemony of knowledge sources exclusively european and north american, mainly in the que regarding the criminalization of processes of analysis occurring in place of Latin America. Allied to Criminology Critical and Criminology Feminist introduced fundamentals concepts brought by decolonial studies as a "colonialidad del Poder" and "colonialidad del Gender" to trace hum more clear theoretical course and substantiating as epistemological reviews made during this work. In this sense, we analyze the Drug Criminal Policy established the level of Latin America and Brazil, racism's relationship with the criminalization of populations exploited those processes of colonial exploitation, and the situation of latin american women imprisoned for drug trafficking crime, a Gender Approach, Race and Class that brings with it a need for substantiating feminisms black, latin american and counter-hegemonic in the Criminology Feminist for what one analyzed to women imprisonment in latin america encompasses own your elements reality , broke with the domination of eurocentric knowledge and has the potential of concrete emancipation.